Management of Fusarium wilt of watermelon (Citrullus lanatus) using Bacillus subtilus and Bacillus cereus - GEETIKA; BUTTAR, DALJEET SINGH; CHOUDHARY, AJAY KUMAR; SINGH, NARINDER (The Indian Journal of Agricultural Sciences, 2024)
Fusarium wilt of watermelon [Citrullus lanatus (Thunb.) Matsumura & Nakai] is caused by Fusarium oxysporum f. sp. niveum (FON), is the most severe soil-borne disease under the prevailing conditions of Punjab. Present study was carried out during 2018–19 and 2019–20 at the pot house and research farm of Punjab Agricultural University, Ludhiana, Punjab to evaluate the antagonistic activity of 15 isolates of Bacillus spp. against FON. These isolates were screened by using dual culture assay and among them, Bacillus subtilus (B1) and Bacillus cereus (B3) showed maximum inhibition percentage i.e. 57.00 and 58.22, respectively. Similarly, these isolates (B1 and B3) showed maximum activity of chitinase (2.31 and 2.16 unit/ml) and glucanase (1.72 and 1.79 unit/ml). Further, Talc-based bio- formulations of B1 and B3 isolates were evaluated in pot house and research farm of Punjab Agricultural University, Ludhiana, Punjab. Amongst all the treatments, Bacillus subtilis (B1) and Bacillus cereus (B3) as seed + soil @15 g treatment showed maximum inhibition of FON. Therefore, based on our findings, Bacillus subtilis (B1) and Bacillus cereus (B3) used as seed + soil treatment was able to effectively manage the fusarium wilt in watermelon under pothouse and field conditions.